2016
DOI: 10.1080/21688370.2016.1187325
|View full text |Cite
|
Sign up to set email alerts
|

Indomethacin induces increase in gastric epithelial tight junction permeability via redistribution of occludin and activation of p38 MAPK in MKN-28 Cells

Abstract: Tight Junctions (TJ) create a paracellular barrier that is compromised when nonsteriodal anti-inflammatory drugs (NSAIDs) injure the gastric epithelium, leading to increased permeability. However, the mechanism of NSAID-induced gastric injury is unclear. Here, we examined the effect of indomethacin on barrier function and TJ in gastric MKN-28 cells. In concentration response studies, 500 µm indomethacin induced a significant decrease in transepithelial resistance (TER; 380 vs. 220 Ω·cm(2) for control and indom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 37 publications
3
13
0
Order By: Relevance
“…We observed a lower expression of stomach OCLN in control-fed or green KF-fed rats with aspirin treatment. This result is supported by the study of Thakre-Nighot et al (2016) who observed a decrease in occludin expression in a gastric cell line and mouse gastric mucosa, with no changes in CLDN 1 or 4 expression, following exposure to the NSAID indomethacin 37 . The positive control drug ranitidine increased stomach CLDN4 expression by 1.8-fold compared with the control in the aspirin-treated rats.…”
Section: Discussionsupporting
confidence: 64%
“…We observed a lower expression of stomach OCLN in control-fed or green KF-fed rats with aspirin treatment. This result is supported by the study of Thakre-Nighot et al (2016) who observed a decrease in occludin expression in a gastric cell line and mouse gastric mucosa, with no changes in CLDN 1 or 4 expression, following exposure to the NSAID indomethacin 37 . The positive control drug ranitidine increased stomach CLDN4 expression by 1.8-fold compared with the control in the aspirin-treated rats.…”
Section: Discussionsupporting
confidence: 64%
“…The activation of the master transcription factor NF-κB has also been evaluated. Both MAPK and NFκB activation have been involved in inflammation-dependent increase of epithelial permeability [42].…”
Section: Resultsmentioning
confidence: 99%
“…3D ) and other reports 33 strongly support that OCLN is not implicated in the regulation of paracellular ion flux. Few reports demonstrate that TER is changed by a decrease in OCLN expression 34 , which may be indirectly caused by the change of CLDNs expression or interaction with an adaptor protein, ZO-1.…”
Section: Discussionmentioning
confidence: 99%